2022
DOI: 10.1177/10775595211072516
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Changes in Parent Sensitivity in Telehealth and Hybrid Implementation of Attachment and Biobehavioral Catch-Up During the COVID-19 Pandemic

Abstract: During the COVID-19 pandemic, home visiting services for families with young children pivoted to continue providing services virtually. One such service was Attachment and Biobehavioral Catch-up (ABC), a brief prevention/intervention program targeting increased parental sensitivity. Seventy families participated in a sensitivity assessment before and after receiving ABC. Forty-three families received the program fully through telehealth, and twenty-seven families received the program through an in-person/teleh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Patterns of autonomic reactivity were similar across home and lab settings (Tabachnick et al, 2022), and community data suggest that intervention fidelity and effects on parenting were maintained in the transition to telehealth (Roben et al, 2022;Schein et al, 2022). Further information regarding RCT enrollment and attrition is provided in Supplement 1.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Patterns of autonomic reactivity were similar across home and lab settings (Tabachnick et al, 2022), and community data suggest that intervention fidelity and effects on parenting were maintained in the transition to telehealth (Roben et al, 2022;Schein et al, 2022). Further information regarding RCT enrollment and attrition is provided in Supplement 1.…”
Section: Methodsmentioning
confidence: 95%
“…Data collection continued with remote assessment only (e.g., interviews by Zoom) until mid‐July 2020, when in‐person data collection resumed on a limited basis, with some families electing remote‐only or home assessments with virtual researcher support. Patterns of autonomic reactivity were similar across home and lab settings (Tabachnick et al., 2022), and community data suggest that intervention fidelity and effects on parenting were maintained in the transition to telehealth (Roben et al., 2022; Schein et al., 2022). Further information regarding RCT enrollment and attrition is provided in Supplement 1.…”
Section: Methodsmentioning
confidence: 97%
“…Prior intervention studies have demonstrated that attachment‐based intervention may reduce adolescents' internalizing and externalizing problems (Moretti et al, 2015 ; Ozturk et al, 2019 ). Although COVID‐19 restrictions may present difficulties for the implementation of interventions, recent research suggests that attachment‐based intervention using remote or hybrid methods can be effective during the pandemic (Levy et al, 2021 ; Schein et al, 2022 ). In addition, the current research highlights the effectiveness and necessity of COVID‐19 communication between parents and adolescents that interventions and policy recommendations should take into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, ABC may be considered a valuable intervention for improving attachment related parent outcomes and consequently a range of child related outcomes among the most vulnerable groups, with Schein et al. (2022) recently highlighting the potential of ABC as a telehealth or hybrid model of intervention, that can adapt to today's changing model of healthcare delivery. Although variability in which attachment related parent outcomes were significantly affected by the ABC intervention was noted, it appeared that all the included studies in this review reach something of a consensus ‐ the ABC intervention positively impacts attachment related parent outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…These effects remained significant at 2 years follow-up. More recently Schein et al (2022) found that when facilitated via telehealth, both exclusively and mixed with face-toface sessions, the ABC intervention was associated with increased parental sensitivity post-intervention highlighting its potential effectiveness in today's changing model of healthcare delivery.…”
Section: Diversity and Anti-racism Statementmentioning
confidence: 99%